DESAIN INTERIOR DALAM KAITANNYA DENGAN SISTEM PELAYANAN PADA RESTORAN GAMBIR SEKETHI DI KUSUMA SAHID PRINCE HOTEL SURAKARTA - Intan Rizki Aprilya; Joko Budiwiyanto (TEXTURE : Art and Culture Journal, 2018)
ABSTRACTKusuma Sahid Prince Hotel is one of the hotels with Javanese-style interiors. Before becoming Kusuma Sahid Hotel, this place was the residence of Prince Kusumoyudo. There are rooms that are still preserved at this hotel, including pendapa functioned as a lobby, pringgitan functioned as the Pantiarjo Room, dalem and krobongan functioned as the Sriwedari Room, four main rooms next to the left and right of the krobongan function as Royal Suites (Presidential Suite ), and left Gandhok functioned as Gambir Sekethi Restaurant. The object of this research is Gambir Sekethi Restaurant which is inside Kusuma Sahid Prince Hotel. Before being used as a restaurant, this space is used for family rooms or dining rooms. The interior design of this restaurant is specially designed with Javanese nuances. This study aims to determine the restaurant service system in relation to spatial layout and interior design of Gambir Sekethi Restaurant in Kusuma Sahid Prince Hotel Surakarta. To achieve the goal, a qualitative descriptive method with an interior design approach is needed. Data sources are informants, literature and objects / artifacts. Data collection techniques using in-depth interviews, literature studies, and observations. The analytical model used is an interactive analysis model. The results of this study indicate that the Gambir Sekethi Restaurant service system can form a layout and circulation that is a unified interior design. This restaurant service system for American service is served by a waiter or waitress and self service. Restaurant layout is made in groups, with the aim of giving guests the freedom to choose the menu served and form regular circulation. The interior design of this restaurant is Javanese style which can be seen from some traditional elements.Keywords: Restaurant Service System, Interior Design of Gambir Sekethi Restaurant, Kusuma Sahid Prince HotelABSTRAKKusuma Sahid Prince Hotel merupakan salah satu hotel dengan interior bergaya Jawa. Sebelum menjadi Hotel Kusuma Sahid, tempat ini merupakan kediaman Pangeran Kusumoyudo. Terdapat ruangan-ruangan yang masih lestari pada hotel ini, di antaranya pendapa dialih fungsikan sebagai lobi, pringgitan difungsikan sebagai Ruang Pantiarjo, dalem dan krobongan difungsikan sebagai Ruang Sriwedari, empat kamar utama di sebelah dalem kiri dan kanan krobongan difungsikan sebagai Royal Suite (Presidential Suite), serta gandhok kiri difungsikan sebagai Restoran Gambir Sekethi. Objek penelitian ini adalah Restoran Gambir Sekethi yang berada di dalam Kusuma Sahid Prince Hotel. Sebelum diguankan sebagai restoran, ruang ini digunakan untuk ruang keluarga atau ruang makan. Desain interior pada restoran ini di desain khusus bernuansa Jawa. Penelitian ini bertujuan untuk mengetahui sistem pelayanan restoran dalam kaitannya dengan tata ruang dan desain interior Restoran Gambir Sekethi di Kusuma Sahid Prince Hotel Surakarta. Untuk mencapai tujuan dibutuhkan penelitian dengan metode kualitatif deskriptif dengan pendekatan desain interior. Sumber data berupa narasumber/informan, literature dan benda/artefak. Teknik pengumpulan data dengan menggunakan wawancara mendalam, studi literature, dan observasi. Model analisis yang digunakan dengan menggunakan model analisis interaktif. Hasil penelitian ini menunjukan bahwa sistem pelayanan Restoran Gambir Sekethi dapat membentuk suatu tata letak dan sirkulasi yang menjadi satu kesatuan desain interior. Sistem pelayanan restoran ini american service dilayani oleh waiter atau waitress dan self service. Layout restoran dibuat perkelompok, dengan tujuan untuk memberikan kebebasan pada tamu dalam memilih menu yang dihidangkan serta membentuk sirkulasi yang teratur. Desain interior restoran ini bergaya Jawa yang dapat dilihat dari beberapa elemen unsur tradisional.Kata Kunci: Sistem Pelayanan Restoran, Desain Interior Restoran Gambir Sekethi, Kusuma Sahid Prince Hotel